Hate speech and discrimination: an overview of the Portuguese situation - Dantas, Carina; Rodrigues, Flávia; Louceiro, Juliana (Technium Social Sciences Journal, 2022)
Fundamental values, such as human dignity, freedom, democracy, equality, and respect for human rights are essential values of a democratic, social and participatory society. Despite this, in the past few years, it is possible to see an increase in hate speech, racism and hate crimes in many countries of the EU. This paper aims to present the state-of-art of the Portuguese situation regarding to discrimination, hate speech and racism, based on literature review of national and international resources, and interviews with persons that have suffered from hate speech, as well as experts in the field. Results forecast a long pathway still to mitigate these phenomena and claim that it is fundamental to have an intervention that includes all societal actors: government, organisations, civil society and citizens. The researchers hope that this paper enriches the knowledge around the concepts discussed and that is useful for the development of strategies towards the promotion of a more equitable society.